2022
DOI: 10.2147/opth.s284609
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Current Management Strategies for Dysthyroid Optic Neuropathy: A Review

Abstract: Dysthyroid optic neuropathy (DON) is a potentially sight-threatening eye disease associated with Graves’ orbitopathy (GO). DON is not common in GO patients, reportedly occurring in only about 5% of patients. The pathogenesis of severe DON is considered to involve both muscular nerve strangulation and impaired blood flow. There is some objective grading of physical examination findings and the severity of GO, including a clinical activity score (CAS) and EUropean Group On Graves’ Orbitopathy (EUGOGO), but no sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 83 publications
0
16
0
1
Order By: Relevance
“…Clinically, Graves' disease (GD) represents the most common form of hyperthyroidism, accounting for 50–80% of all cases ( 1 , 2 ), and the incidence of GD has been increasing over the past few years ( 1 , 3 ). Over 30% of patients with GD suffered from Graves' orbitopathy (GO) ( 4 6 ), which caused vision loss ( 7 ). Additionally, it has been reported that GD was associated with the incidence of major adverse cardiac events (MACE) ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, Graves' disease (GD) represents the most common form of hyperthyroidism, accounting for 50–80% of all cases ( 1 , 2 ), and the incidence of GD has been increasing over the past few years ( 1 , 3 ). Over 30% of patients with GD suffered from Graves' orbitopathy (GO) ( 4 6 ), which caused vision loss ( 7 ). Additionally, it has been reported that GD was associated with the incidence of major adverse cardiac events (MACE) ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the occurrence of DON is noted only in 5%–7% of TED cases. [ 2 ] The diagnosis of established DON is majorly clinical, but the diagnosis of subclinical DON may need detailed ophthalmic examination and imaging. Patients with subclinical DON may not experience a sudden diminution of vision, abnormal pupillary reflexes, and features of orbital inflammation—classical of severe TED.…”
mentioning
confidence: 99%
“…Patients with subclinical DON may not experience a sudden diminution of vision, abnormal pupillary reflexes, and features of orbital inflammation—classical of severe TED. [ 2 ]…”
mentioning
confidence: 99%
See 2 more Smart Citations